1999
DOI: 10.1161/01.cir.100.6.628
|View full text |Cite
|
Sign up to set email alerts
|

Reflex Control of Sympathetic Activity During Simulated Ventricular Tachycardia in Humans

Abstract: Background-Ventricular tachyarrhythmias present a unique set of stimuli to arterial and cardiopulmonary baroreceptors by increasing cardiac filling pressures and decreasing arterial pressure. The net effect on the control of sympathetic nerve activity (SNA) in humans is unknown. The purpose of this study was to determine the relative roles of cardiopulmonary and arterial baroreceptors in controlling SNA and arterial pressure during ventricular pacing in humans. Methods and Results-Two experiments were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…We recently showed that SNA response during VP was mediated primarily by the arterial baroreflex and that it was modulated by input from cardiopulmonary baroreceptors. 3 Our findings are consistent with those of Landolina et al 14 : baroreflex gain was markedly reduced in patients with poorly tolerated VP, suggesting that baroreflex gain is an important determinant of BP recovery during VP. In our study, baroreflex-SNA gain was a better predictor than baroreflex-HR gain.…”
Section: Autonomic Changes During Vt/vpsupporting
confidence: 93%
See 4 more Smart Citations
“…We recently showed that SNA response during VP was mediated primarily by the arterial baroreflex and that it was modulated by input from cardiopulmonary baroreceptors. 3 Our findings are consistent with those of Landolina et al 14 : baroreflex gain was markedly reduced in patients with poorly tolerated VP, suggesting that baroreflex gain is an important determinant of BP recovery during VP. In our study, baroreflex-SNA gain was a better predictor than baroreflex-HR gain.…”
Section: Autonomic Changes During Vt/vpsupporting
confidence: 93%
“…4,17 Nevertheless, studies in both dogs and humans have shown that in patients with the substrate for VT, arterial baroreflexes tend to predominate in the control of SNA. 3,4 The present study extends these findings to show that arterial baroreflex gain is a predictor of hemodynamic outcome during ventricular tachyarrhythmias.…”
Section: Autonomic Changes During Vt/vpsupporting
confidence: 75%
See 3 more Smart Citations